Averaging Method for Neutral Stochastic Delay Differential Equations Driven by Fractional Brownian Motion. (29th May 2020) - Wang, Peiguang; Xu, Yan
Abstract : In this paper, we investigate the stochastic averaging method for neutral stochastic delay differential equations driven by fractional Brownian motion with Hurst parameter H ∈ 1 / 2, 1 . By using the linear operator theory and the pathwise approach, we show that the solutions of neutral stochastic delay differential equations converge to the solutions of the corresponding averaged stochastic delay differential equations. At last, an example is provided to illustrate the applications of the proposed results.